Understanding the Management of High Impact Publication Education Journals; An International Journal Publication Analysis Study - Sudarmo Sudarmo; Pandu Adi Cakranegara; Fitri Yulia; Fina Amalia Masri (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
One of the tasks of academics such as lecturers or researchers in universities is writing research papers and giving seminars to academic audiences. For the results of published articles to be published quickly, the review factor of the form must be of high value based on the peer-reviewed rating of the journal editor and the blind review system. However, all academics are well aware of the indicators of high impact factors. Therefore, we present this study intending to gain an in-depth understanding of the issues of these high impact factors. We have reviewed around 50 articles. We have given the results as findings that include, among others, high impact journals frequently cited across the academic spectrum, mainly when discussed in other high impact journals. The citation index was first developed in the 1950s to determine journal 'Impact Factors.' In other words, those journals with a score of 10 or more are considered excellent in most categories; a score of 3 is deemed to be adequate, and an average score of less than one. This is a rule of thumb. One caveat to keep in mind is that impact factors and journal comparisons work best when applied to the same field.